2022
DOI: 10.5650/jos.ess21281
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of <i>Gynostemma pentaphyllum</i> against Streptozotocin Induced Cardiac Toxicity in Rats via Alteration of AMPK/Nrf2/HO-1 Pathway

Abstract: IntroductionDiabetes mellitus (DM) has emerged as a global health issue that poses a risk to human health 1) . DM is a metabolic dysfunction that induces a defect in insulin action or insulin secretion from the pancreatic β-cells, which results in hyperglycemia with commotion of protein, carbohydrate and fat metabolism 2) . Due to disturbances in metabolism, DM leads to chronic complications include cardiomyopathy, nephropathy, retinopathy and neuropathy 3,4) . Among of them complications, cardiomyopathy (DC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The Nrf2-dependent antioxidant response is a well-known protective mechanism against cardiovascular diseases and insults, including myocardial infarction [49], aortic stenosis [50], streptozotocininduced cardiac toxicity [51], myocardial ischemia reperfusion injury [52], diabetic cardiomyopathy [53], and atherosclerosis [54]. Likewise, several studies reported that during septic cardiomyopathy, Nrf2 activity protects heart function via multiple mechanisms [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2-dependent antioxidant response is a well-known protective mechanism against cardiovascular diseases and insults, including myocardial infarction [49], aortic stenosis [50], streptozotocininduced cardiac toxicity [51], myocardial ischemia reperfusion injury [52], diabetic cardiomyopathy [53], and atherosclerosis [54]. Likewise, several studies reported that during septic cardiomyopathy, Nrf2 activity protects heart function via multiple mechanisms [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have used STZ to model diabetes cardiomyopathy in rats [ 15 , 16 , 17 ]. In this diabetic cardiomyopathy rat model, elevated ROS levels are presented with higher MDA levels and decreased antioxidant—such as SOD, GPx and Nrf2—expression, which then induced cardiac cell damage [ 1 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can decrease the production of antioxidant enzymes such as SOD, GPx and Catalase. Nfr2 is an essential transcription factor that controls the response of antioxidants for maintenance in homeostasis on cellular redox [ 5 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations